(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Tuberculosis (TB) still remain a major challenging global health problem. India is one the high TB burden country, adding to 26 per cent of the worldwide TB burden. During the 20th century, TB became treatable and the therapeutic success of short-course chemotherapy was a break through. In the early 1980s, human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS) pandemic resulted in a resurgence of TB globally with more complications and challenges like occurrence of multidrug-resistant and extensively drug-resistant TB (M/XDR-TB). Atypical clinical presentation still poses a challenge. While treatment of TB and HIV-TB co-infection has become simpler, efforts are on to shorten the treatment duration. However, drug toxicities, adverse drug reactions and drug-drug interactions still possess a significant challenge. Hurdles like the lack of adequate coverage, low economy and weak health services limit access to high-quality tuberculosis care in some of the countries. Further, many public and private health-care providers remain delinked from national tuberculosis control efforts. In addition, tuberculosis is a disease of the poor and the absence of universal health coverage aggravates the economic burden of TB on the poor. Even though the advancements in tuberculosis control over the past two decades are strong, relatively high effort is needed to wipe out the pandemic. A pursuit for novel biomarkers for predicting a durable cure, relapse, discovery/repurposing of newer anti-TB drugs, development of newer vaccines continues to attain the goal of eliminating TB altogether by 2050. The present review focuses on the global and Indian tuberculosis situation. It emphasizes the epidemiological situation in India and the burden of disease in the nation over time.